SOME ASPECTS OF THE IMPACT OF ALGORITHMIC SYSTEMS ON THE OVERALL TAX COMPETITIVENESS INDEX IN TAXATION ISSUES - Sh.V. Ganiyev; B. B. Ibragimov (American Journals, 2024)
Research carried out by the International Center for tax and development (ICTD) has shown that only 23% of developing countries have approved a strategy for digitalization and development of tax administration. But in the context of the digital economy, the issues of improving the elements of tax administration are poorly studied as a holistic system in the direction of automation and digital transformation, as a scientific study. The purpose of the study is to develop proposals for improving the organizational elements of tax administration and increasing the level of cooperation between taxpayers and tax authorities.
Keywords: Tax administration, taxes, index, algorithmic